I santi degli altri. Devozione, mutamento e rituali tra i singalesi cattolici a Messina - Giovanni Cordova (Archivio Antropologico Mediterraneo)
In this article I examine changes occurring in rituals and devotional practices enacted by Sinhala Catholics living in Messina (Sicily) and including new saint figures in their devotional repertoires in the wake of transnational mobility. For this reason, processes of construction of sainthood at the core of these ritual systems, very useful to reflect upon the vernacularization of religious discourses along the post-colonial trajectories of western “multicultural” Church, will be analyzed looking at the interactions connecting them to ecclesial powers, the daily experience of the sacred, and religious actors’ existential and biographical paths. Sinhala Catholics living in Messina are now deeply grounded in the local migration landscape. In the last years they have been progressively institutionalized their religious belonging through stable connections (although subject to continuous negotiation) with Messina’s Catholic diocese. Drawing on an ethnographic research focused on home-making processes activated through ritual practices and activities, I will take into account two examples of ritual complexes that are centered on saint figures that the Sinhalese meet and discover during their transnational mobility (as in the case of Saint Elia) or towards whom devotion is not so much rooted in Sri Lanka, being rather fed by the Messina’s Church (as in the case of Saint James). In both cases, these “saints of the others” must be placed and understood in the context of social and political relations within which devotional idioms and cultural repertoires take shape.